Recurrence rate and shift in histopathological differentiation of oral squamous cell carcinoma – A long-term retrospective study over a period of 13.5 years. Issue 7 (September 2015) - Ermer, M.A.; Kirsch, K.; Bittermann, G.; Fretwurst, T.; Vach, K.; Metzger, M.C.
Abstract Objective Little information is available as to whether recurrences of oral squamous cell carcinoma (OSCC) show different histopathological grades than the primary tumor and whether postoperative radiotherapy (PORT) influences the grade of differentiation in the case of recurrence. The objective of this study was the evaluation of recurrence rates and change in differentiation. Material and methods This retrospective, single-institution cohort study included surgically treated OSCC patients over a 13-year period (2000–2013). The relationship among tumor size, lymph node metastases, and recurrence rate of OSCC was investigated. Primary tumor differentiation was compared with differentiation of recurrence. Results A total of 429 patients (277 men and 152 women) were included in this study. Of these, 124 (28.9%) received PORT. The incidence of primary cervical metastases increased significantly with tumor size (p < 0.001). Recurrence developed in 82 patients (19.1%). Stage T1/T2 showed a significantly lower recurrence rate than stage T3/T4 (16.3% vs. 30.2%) (p < 0.01). A total of 23 (30.7%) patients with recurrence showed a change in differentiation. Conclusion Increasing primary tumor size correlates with incidence of cervical metastases and recurrence rate. Initial cervical metastases show no effect on recurrence rates. Differentiation of primary tumor does not correlate with the recurrence rate. The majority of recurrences show consistent histopathological grading.